Enhancing Reading Literacy and Self-Efficacy in Elementary Students: Development of Generative AI Assisted Interactive E-Module: Meningkatkan Literasi Membaca dan Efikasi Diri pada Siswa Sekolah Dasar: Pengembangan E-Modu Interaktif Berbantuan Generative-AI - M Yuman Hidayat; Banu Setyo Adi (ITScience (Information Technology and Science), 2026)
The primary objective of this study was to determine the feasibility, practicality, and effectiveness of the generative-AI-assisted interactive e-module designed to improve elementary school students’ reading literacy skills and self-efficacy. Product development followed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), with a sample of 54 fifth-grade students, using a quasi-experimental design with a non-equivalent pretest-posttest control group. Data collection instruments included validation sheets, tests, and questionnaires, and data analysis used descriptive and inferential statistical techniques. The research findings indicate that the generative-AI-assisted interactive e-module is highly valid based on validations by media experts (91.66%) and content experts (91.25%); highly practical based on teacher feedback (93.25%); and effective, supported by statistical analysis results showing a significance value of 0.000 (< 0.05). Thus, the product is deemed feasible, practical, and effective in increasing elementary school students’ reading literacy skills and self-efficacy. These findings reinforce the value of innovation in improving the quality of learning media and provide insights for teachers seeking to create more adaptive, learner-centred digital media. Future studies are expected to integrate more diverse content, test the product’s effectiveness across various educational levels, and optimise interactive features and generative AI.